Comparative Study of the Effects of 1% Atropine on the Anterior Segment - Yue Zhou; Xiao Bo Huang; Qi Cai; Jun Jie Li; Yao Jia Xiong; Ye Xun Gong; Li Wei Lin; Yan Zhu; Zhi Min Sun (Journal of Ophthalmology)
Purpose. To investigate the influences of atropine on changes in anterior segment geometry, as measured by ultrasound biomicroscopy in children. Methods. A prospective observational study was performed. Anterior segment parameters were obtained by UBM before and after the instillation of 1% atropine. Univariate linear regression was performed to identify the variables contributing to the changes in the trabecular meshwork-iris angle (TIA). Results. The study included 21 boys and 37 girls with a mean age of 10.79 ± 2.53 years. Anterior chamber parameters including the central anterior chamber depth, TIA, angle opening distance at 500 μm from the scleral spur, iris thickness 750 μm and 1500 μm from the scleral spur, trabecular-ciliary angle (TCA), trabecular-ciliary process distance, sclera-iris angle (SIA), and sclera-ciliary process angle significantly increased after cycloplegia (P<0.05). In contrast, the lens vault, iris cross-sectional area, and maximum ciliary muscle thickness significantly decreased after cycloplegia. Univariate analysis identified the change in TCA and the change in SIA and the TIA before mydriasis as determinants of the change in TIA. Conclusions. Atropine causes statistically significant changes in various anterior segment parameters in children. The change in anterior chamber angle is associated with the change in TCA and the change in SIA and the TIA before mydriasis.